The effect of chloride ions and A. ferrooxidans on the oxidative dissolution of the chalcopyrite evaluated by electrochemical noise analysis (ENA) - Horta, D. G. [UNESP]; Acciari, H. A. [UNESP]; Bevilaqua, D. [UNESP]; Benedetti, Assis Vicente [UNESP]; Garcia, O. [UNESP] (Trans Tech Publications, 2009)
It is believed that the dissolution of chalcopyrite (CuFeS2) in acid medium can be accelerated by the addition of Cl- ions, which modify the electrochemical reactions in the leaching system. Electrochemical noise analysis (ENA) was utilized to evaluate the effect of the Cl- ions and Acidithiobacillus ferrooxidans on the oxidative dissolution of a CPE-chalcopyrite (carbon paste electrode modified with chalcopyrite) in acid medium. The emphasis was on the analysis of the admittance plots (Ac) calculated by ENA. In general, a stable passive behavior was observed, mainly during the initial stages of CPE-chalcopyrite immersion, characterized by a low passive current and a low dispersion of the Ac plots, mainly after bacteria addition. This can be explained by the adhesion of bacterial cells on the CPE-chalcopyrite surface acting as a physical barrier. The greater dispersions in the Ac plots occurred immediately after the Cl- ions addition, in the absence of bacteria characterizing an active-state. In the presence of bacteria the addition of Clions only produced some effect after some time due to the barrier effect caused by bacteria adhesion. © (2009) Trans Tech Publications.
Keywords: Admittance; Bioleaching; Chalcopyrite; Electrochemical noise analysis; Acid medium; Acidithiobacillus ferrooxidans; Bacterial cells; Barrier effects; Carbon paste electrode; Chloride ions; Cl- ions; Electrochemical Noise Analysis; Electrochemical reactions; Ferrooxidans; Initial stages; Oxidative dissolution; Passive behavior; Physical barriers; Acids; Adhesion; Bacteriology; Cell adhesion; Chlorine compounds; Copper compounds; Dispersions; Dissolution; Electric network analysis; Ions; Surface chemistry; Metal recovery